Analisis Pengaruh Dukungan Universitas, Dukungan Keluarga dan Efikasi Diri terhadap Minat Berwirausaha (Studi pada Mahasiswa Penerima PMW di Jawa Timur) - Bima Setyo Nugroho; Rara Anggraini; Mazaya Najmy Tsaqyfa; Suprihatin; Ahmad Ajib Ridlwan (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2024)
This ponder looks at the impact of college bolster, family back, and self-efficacy on the entrepreneurial intrigued of East Java PMW beneficiary understudies. A quantitative strategy was utilized in this think-about. The investigation test comprised 248 PMW beneficiaries. Coincidental Inspecting carried out test determination. Information investigation was carried out utilizing SEM-PLS through the SmartPLS 3.2.9 program. The study shows that (1) College back has no critical impact on entrepreneurial intrigue. (2) Family bolster encompasses a positive impact on entrepreneurial intrigue. (3) Self-efficacy incorporates a positive impact on entrepreneurial intrigue. The study shows that superior colleges cultivate students' entrepreneurial curiosity. Family back and self-efficacy are imperative components in empowering entrepreneurial intrigue among understudies. Suggestions and headings for future investigation are also discussed.